Assessing PTSD in the military: Validation of a scale distributed to Danish soldiers after deployment since 1998. Issue 3 (18th April 2017) - Karstoft, Karen‐Inge; Andersen, Søren B.; Nielsen, Anni B. S.
Abstract : Since 1998, soldiers deployed to war zones with the Danish Defense (≈31, 000) have been invited to fill out a questionnaire on post‐mission reactions. This provides a unique data source for studying the psychological toll of war. Here, we validate a measure of PTSD‐symptoms from the questionnaire. Soldiers from two cohorts deployed to Afghanistan with the International Security Assistance Force (ISAF) in 2009 (ISAF7, N = 334) and 2013 (ISAF15, N = 278) filled out a standard questionnaire (Psychological Reactions following International Missions, PRIM) concerning a range of post‐deployment reactions including symptoms of PTSD (PRIM‐PTSD). They also filled out a validated measure of PTSD‐symptoms in DSM‐IV, the PTSD‐checklist (PCL). We tested reliability of PRIM‐PTSD by estimating Cronbach's alpha, and tested validity by correlating items, clusters, and overall scale with corresponding items in the PCL. Furthermore, we conducted two confirmatory factor analytic models to test the factor structure of PRIM‐PTSD, and tested measurement invariance of the selected model. Finally, we established a screening and a clinical cutoff score by application of ROC analysis. We found high internal consistency of the PRIM‐PTSD (Cronbach's alpha = 0.88; both cohorts), strong item‐item (0.48–0.83), item‐cluster (0.43–0.72), cluster‐cluster (0.71–0.82) and full‐scale (0.86–0.88) correlations between PRIM‐PTSD and PCL. The factor analyses showed adequate fit of a one‐factor model, which was also found to display strong measurement invariance across cohorts. ROC curve analysis established cutoff scores for screening (sensitivity = 1, specificity = 0.93) and clinical use (sensitivity = 0.71, specificity = 0.98). In conclusion, we find that PRIM‐PTSD is a valid measure for assessing PTSD‐symptoms in Danish soldiers following deployment.